Analysis of the Implementation of PSAP No. 05 in Inventory Accounting at the Food Security and Livestock Service of Jember Regency: English - Diva Candra Rista; Diana Dwi Astuti; Ratih Rakhmawati (Journal of Management, 2025)
Abstract This study aims to analyze the implementation of Government Accounting Standards Statement (PSAP) No. 05 in the accounting treatment of inventory at the Regional Government Office of the Food Security and Livestock Service in Jember Regency. The research employs a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with selected informants. The findings indicate that the inventory accounting treatment at the Food Security and Livestock Service Office of Jember Regency is in accordance with PSAP No. 05. In terms of recognition, inventory is acknowledged when the goods are received along with all required documentation, and stock-taking is conducted every three months. For measurement, inventory is recorded at acquisition cost, which is obtained through purchases using the FIFO method. However, in terms of disclosure and reporting, there are still shortcomings in complying with PSAP No. 05, due to a lack of detailed explanation and inventory reporting. The implications of these findings suggest that although the implementation of PSAP No. 05 is generally well-executed, there remains a need to enhance human resource capacity and understanding to support more optimal inventory management.